The perfils of crossing borders: the financial constraints of brazilian exporters during the 2009 global trade collapse - Carneiro, Stella Mendes (2018)
This paper explores the 2008-2009 Global Trade Collapse to estimate the effects of a credit supply shock on exporters\' investments decisions. Using a Brazilian firm-level dataset compiled by the Brazilian Internal Revenue Service (IRS) over the period 2007-2013, I pair up export-intensive firms with their domestically-oriented counterparts to, subsequently, calculate the differences in terms of sensitivity of investment to cash flow between the two groups over the years. After controlling for the effect of international falling demand, my study reveals that exporters are more severely constrained than their peers in the control group only in 2009, when the supply of credit instruments to finance international trade shrank. Given their high need of external financing to support exporting activities and the volatility of the cost of trade finance, usually priced against 3-month Libor, my results are in line with expected. A number of robustness and placebo tests confirm the validity of the findings.